Elasticsearch the definitive guide - Gormley, Clinton; Tong, Zachary (O'Reilly Media, 2015)
Whether you need full-text search or real-time analytics of structured data-or both-the Elasticsearch distributed search engine is an ideal way to put your data to work. If you're a newcomer to both search and distributed systems, you'll quickly learn how to integrate Elasticsearch into your application. More experienced users will pick up lots of advanced techniques. Throughout the book, you'll follow a problem-based approach to learn why, when, and how to use Elasticsearch features.